A model of austrian economics - Hagedorn, Hendrik (Springer Fachmedien Wiesbaden Imprint: Springer Gabler, 2015)
After the most recent financial crisis it has become clear that there exists a crisis also in economics as a science. The prevailing paradigms have failed to anticipate and to understand the financial crisis. New approaches are therefore needed. Of particular interest should be approaches that combine insights from those parts of economics that are largely neglected by the mainstream. Hendrik Hagedorn presents a model that synthesizes elements of Austrian, post-Keynesian, and evolutionary economics. Thus, an economic paradigm is developed that challenges neoclassical economics as a whole.  Contents An agent-based economy within an accounting framework  Reaction algorithms for households, firms, and banks A contribution to interest-rate theory  A comparison of Austrian and neoclassical economics  Target Groups Students and researchers in the fields of economics and epistemology of the social sciences  Macroeconomic analysts  The Author Hendrik Hagedorn is a physicist and an economist. He works at an institute for applied economic research in Germany.